2010
DOI: 10.4137/cmo.s6163
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cell Adenocarcinoma in the Tongue: An Unusual Presentation

Abstract: We present a case of basal cell adenocarcinoma (BCAC) in the tongue in a 65-year old male. This is an extremely rare presentation. BCAC generally occurs in the parotid gland and rarely involves the minor salivary glands. Few cases have been reported in literature with a variable presentation. The biopsy was formalin-fixed and paraffin-embedded. The sections were stained with routine Hematoxylin and Eosin. Immunohistochemistry was performed. Hematoxylin and eosin staining showed tumour composed of variable size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Andraedis et al found that both BCA and BCAC had similar architectural and cytologic factors and were not differentiable by ultrastructural or immunohistochemical examinations [8]. However, other researchers have found certain immunohistochemical markers that may play a role in the diagnosis of BCAC (Table I) [3,4,5]. It is important to distinguish BCAC from other lesions such as basal cell adenoma, basaloid squamous cell carcinoma, myoepithelial lesions, Warthin tumour, pleomorphic adenoma, small cell undifferentiated carcinoma, metastatic adenocarcinoma and adenoid cystic carcinoma due to the difference in treatment and prognosis among these lesions [3,4,5,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Andraedis et al found that both BCA and BCAC had similar architectural and cytologic factors and were not differentiable by ultrastructural or immunohistochemical examinations [8]. However, other researchers have found certain immunohistochemical markers that may play a role in the diagnosis of BCAC (Table I) [3,4,5]. It is important to distinguish BCAC from other lesions such as basal cell adenoma, basaloid squamous cell carcinoma, myoepithelial lesions, Warthin tumour, pleomorphic adenoma, small cell undifferentiated carcinoma, metastatic adenocarcinoma and adenoid cystic carcinoma due to the difference in treatment and prognosis among these lesions [3,4,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…The membranous type is characterised by large amount of PAS positive, hyalinised eosinophilic basal lamina that forms the peripheral membrane and intercellular droplets. The trabecular type contains basaloid cells that form interconnecting bands [5]. Andraedis et al found that both BCA and BCAC had similar architectural and cytologic factors and were not differentiable by ultrastructural or immunohistochemical examinations [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations